Ekstrakulikuler Pramuka Sebagai Konstruksi Dasar Penguatan Karakter dalam Meningkatkan Toleransi Siswa MTs Harsalakum Kota Bengkulu - Soffiah Lauwren BR. Sitorus Pane (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
This research is motivated by observational data which shows the results obtained from the implementation of extracurricular scouting at MTs Harsalakum, Bengkulu City. Students are taught to have an attitude of tolerance towards fellow friends, be religious, care and so on. As for the other characters, the students at MTs Harsalakum, Bengkulu City are already good. This is demonstrated by the students by maintaining school cleanliness, respecting teachers, praying when carrying out all activities. However, regarding discipline in its implementation, students still do not have an attitude of tolerance as explained by the instructor. The aim to be achieved is to find out, describe and analyze the process, training and basic construction of character formation in increasing student tolerance through scouting extracurriculars at MTs Harsalakum, Bengkulu City. This research is descriptive qualitative research. This research was conducted on students at MTs Harsalakum, Bengkulu City. Research data was obtained from observation, interviews and documentation. The results of this research are the process of character building in strengthening students' tolerance through scout extracurriculars at MTs Harsalakum, Bengkulu City. In the process of implementing scout extracurriculars at MTs Harsalakum, Bengkulu City, students are taught to have an attitude of tolerance towards fellow friends, religious, caring and so on. As for the other characters, the students at MTs Harsalakum, Bengkulu City are already good. This is demonstrated by the students by maintaining school cleanliness, respecting teachers, praying when carrying out all activities. Forms of training for extracurricular activities for Scouts at MTs Harsalakum, Bengkulu City to form character in strengthening tolerance, namely Forming Good Behavior, Forming an Orderly Personality, Creating Fun Activities, Providing Knowledge, Giving Warnings, Cultivating Obedient Attitudes. The basic construction of character formation in strengthening tolerance at MTs Harsalakum, Bengkulu City, is that the instructors give punishments such as sweeping the room after scout training is finished, reciting the Scout Dasa Darma, and so on.